Impact of Tsunami on the Heavy Metal Accumulation in Water, Sediments and Fish at Poompuhar Coast, Southeast Coast of India - P. Martin Deva Prasath; T. Hidayathulla Khan (E-Journal of Chemistry)
Investigations on the accumulation of heavy metals (Zn, Cu, Fe, Mn, Co, Pb, Cd and Ni) in water, sediments and fish (Mugil cephalus) using Atomic Absorption Spectrophotometer at Poompuhar coast, lying along the southeast coast of India was studied before and after tsunami. Accumulation of heavy metals was observed in the order of Sediments > Fish > Water. In water, the order was found to be Mn > Fe > Zn > Cu > Ni > Cd > Co > Pb; Mn recorded a maximum of 506.9µ. L-1 and Pb recorded a minimum of 0.006µ. L-1 . In sediments, the order was Mn > Fe > Cu > Zn > Pb ≈Co ≈Cd ≈ Ni; Mn recorded a maximum of 851.1µg.g-1 and a minimum of below detectable levels were found in Pb, Co, Cd and Ni. In fish, the order was found to be Fe > Zn > Mn > Cu > Ni > Co ≈ Pb ≈ Cd; Fe recorded a maximum of 529.13 µg. g-1 and a minimum of below detectable levels were found in Pb and Cd.